Readings in Christian thought (Abingdon Press, 1966)
This volume provides a source treasury for the history and development of Christian theology. It has in view the student, the teacher of religion in college or divinity school, the chaplain in armed services or institution, the clergyman and preacher, the adult church study group, and the self-taught layman. In the selections that follow, many theological controversies are paraded along the march of history. The unity that ties them together is the persuasion that Christian faith demands not only devotion and obedience but solid thinking and honest questioning.